Computation of Reliability, Average Reliability, and Maintainability of Service Demand Fulfilment Dynamically using System Dynamics - Mudjahidin, Mudjahidin; Buliali, Joko Lianto; Yuniarto, Muhammad Nur; Suryani, Erma (International Journal of Supply Chain Management, 2019)
An enterprise not only need information about the time-based service performance (reliability and maintenance of services) but also need to know the effect of time variables on service performance and demand dynamically so as to determine the right service time to providing the services level. This article proposes system dynamics approach to simulate the reliability, average reliability and maintainability of services and enterprise based on service time of demand fulfillment. The model created is a dynamic model that forms a closed system containing negative feedbacks that can be used to simulate. Generally, in a dynamic model with negative feedback, the decrease of time variable causes the increase of reliability of service. However, the simulation scenarios of the dynamic model with negative feedbacks in this article show the decrease of time variables (service time of demand fulfillment and its meantime, meantime of reliability function) can cause either decrease, increase or no change to the total of demand as well as number and average of demand reliability, average reliability, and maintainability in the enterprise.